Democracy, culture, and contagion: political regimes and countries responsiveness to Covid-19 - Frey, CB; Chen, C; Presidente, G (Centre for Economic Policy Research, 2020)
A widely held belief is that autocratic governments have been more effective in reducing the movement of people to curb the spread of Covid-19. Using the Oxford COVID-19 Government Response Tracker (OxCGRT), and a real-time dataset with daily information on travel and movement across 111 countries, we find that autocratic regimes imposed more stringent lockdowns and relied more on contact tracing. However, we find no evidence that autocratic governments were more effective in reducing travel, and evidence to the contrary: countries with democratically accountable governments introduced less stringent lockdowns but were approximately 20% more effective in reducing geographic mobility at the same level of policy stringency. In addition, building on a large literature on cross-cultural psychology, we show that for the same policy stringency, countries with more obedient and collectivist cultural traits experienced larger declines in geographic mobility relative to their more individualistic counterparts. We conclude that, in terms of reducing mobility, collectivist and democratic countries have implemented relatively effective responses to Covid-19.